Step 1: Substituting \( t = e^{2x} \).
Let:
\[
t = e^{2x} \Rightarrow dt = 2e^{2x} dx = 2t \, dx.
\]
Rewriting the integral:
\[
I = \int \frac{e^{2x} - 1}{e^{2x} + 1} \, dx.
\]
Step 2: Splitting the fraction.
Rewrite the numerator:
\[
e^{2x} - 1 = (e^{2x} + 1) - 2.
\]
Thus, the integral becomes:
\[
I = \int \frac{(e^{2x} + 1) - 2}{e^{2x} + 1} \, dx.
\]
Splitting:
\[
I = \int \left( 1 - \frac{2}{e^{2x} + 1} \right) dx.
\]
Step 3: Solving the integral.
The first term:
\[
\int 1 \, dx = x.
\]
For the second term, let:
\[
t = e^{2x} + 1 \Rightarrow dt = 2e^{2x} dx = 2(t - 1) dx.
\]
Rearrange:
\[
dx = \frac{dt}{2(t - 1)}.
\]
Thus:
\[
\int \frac{2}{e^{2x} + 1} \, dx = \int \frac{2}{t} \cdot \frac{dt}{2} = \int \frac{dt}{t} = \log |t|.
\]
Substituting back \( t = e^{2x} + 1 \):
\[
\log |e^{2x} + 1|.
\]
Step 4: Conclusion.
\[
I = \log (e^{2x} + 1) - x + C.
\]
Thus, the correct answer is \( \mathbf{\log (e^{2x} + 1) - x + C} \).